(3RHOI GrdncndGe paj oMoUhd GdeQGes - (3GdQhej GdMfaj, hdj GdOjf, aQjOj, eMeO Hf YHO Gddg (B, 1082s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd ChQGb GdCTLGQ YHQI dChdj GdCHUGQ bO JNGdL aj bdHj ReGfG Cf CTQM CHjGJ SYOj CMOgG aj CTYGQ GdJhMjO hKGfjgG GeGQI aj JUdjI GdfHj GdeNJGQ hKGdKgG jMO QSe GdGfUGa hQGHYgG jHjf GdJhcd Ydi hLg GdGYJQGas
(3BNQgG (B:s
(3bGd CHh GdYJGgjI (B: (3Edgj dG JYPHfj aEfj ebQ HGdPj bO cGf efj aeG dj MjdI EdG QLGFj dYahc Ef YahJ hMSf Xfj jXf GdfGS Hj NjQG hEfj dTQ GdfGS Ef de JYa Yfj JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/439s
(3gOjI GdYGQajf (B2/293s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds